2015
DOI: 10.1002/adma.201503500
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Piezo‐Phototronic‐Effect‐Enhanced Light‐Emitting Diodes and Pressure Imaging

Abstract: Wurtzite materials exhibit both semiconductor and piezoelectric properties under strains due to the non-central symmetric crystal structures. The three-way coupling of semiconductor properties, piezoelectric polarization and optical excitation in ZnO, GaN, CdS and other piezoelectric semiconductors leads to the emerging field of piezo-phototronics. This effect can efficiently manipulate the emission intensity of light-emitting diodes (LEDs) by utilizing the piezo-polarization charges created at the junction up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 120 publications
(105 reference statements)
0
72
0
Order By: Relevance
“…The piezo‐phototronic effect refers to the use of piezo‐polarization charges created inside some wurtzite materials, such as CdS, CdSe, GaN and ZnO, to regulate the energy bands and engineer the charge carriers in optoelectronic processes, such as generation, separation, transportation and recombination, at the metal‐semiconductor interface or the p‐n junction . This effect has been widely explored recently by combing with flexible optoelectronics technology with the aim to enhance the performance of optoelectronic devices such as solar cells, light‐emitting diodes and photodetectors, etc.…”
Section: D Inorganic Nanostructures‐based Flexible Photodetectorsmentioning
confidence: 99%
“…The piezo‐phototronic effect refers to the use of piezo‐polarization charges created inside some wurtzite materials, such as CdS, CdSe, GaN and ZnO, to regulate the energy bands and engineer the charge carriers in optoelectronic processes, such as generation, separation, transportation and recombination, at the metal‐semiconductor interface or the p‐n junction . This effect has been widely explored recently by combing with flexible optoelectronics technology with the aim to enhance the performance of optoelectronic devices such as solar cells, light‐emitting diodes and photodetectors, etc.…”
Section: D Inorganic Nanostructures‐based Flexible Photodetectorsmentioning
confidence: 99%
“…Luminescent stimuli-responsivem aterials that exhibit modulation of their emission properties are of particular interest for the development of multifunctionala ctive materials with main applicationsi nt he field of detection. [1][2][3][4][5][6] Modification of the luminescence properties of molecular materials is often the consequence of environmental changes to the molecular entities. Compounds that exhibit aggregation-induced emission (AIE) properties are perfect illustrations of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…1D semiconductor nanostructures (typically nanowires) have witnessed tremendous development over the past two decades owing to their potential applications, which range widely from electrical to mechanical devices . Many works have reported that the high elastic limit of nanowires (NWs) leads to a larger tunable bandgap range in comparison to that of their bulk counterparts .…”
Section: Introductionmentioning
confidence: 99%